IMPLEMENTASI PENDIDIKAN ANAK USIA DINI DENGAN PENDEKATAN BIMBINGAN KONSELING - Dessy Syofiyanti; Baiq Mahyatun (STKIP PGRI Situbondo, 2022)
The development of children's talents and interests would be better done early on, one of which, of course, starts from schools based on early childhood education with various levels of programs, in the application of teaching to children from an early age, of course it is very necessary to develop self through activities based on counseling guidance so that Children grow and develop both intellectually, emotionally and socially. This study aims to discuss the implementation of early childhood education with a counseling guidance approach, a case study conducted in one of the early childhood education schools (PAUD) located in Indragiri Hulu (INHU) Regency, Riau. Based on the results of the study, this early childhood education not only applied Islamic education but also began to apply the guidance and counseling approach, in its teaching, although its weakness, it did not have educators who graduated from early childhood and counseling guidance. Overall, the implementation of counseling guidance in this school has started to run, has not been equipped with facilities and infrastructure, but this school has the creativity to cover this shortcoming.